Pengujian Awal Potensi Tanaman Lidah Mertua (Sansevieria trifasciata) dalam Pemanfaatannya sebagai Fitoremediasi terhadap Tanah yang Tercemar Logam Cu - Andi Badli Rompegading; Dewi Sartika; Rani Sengka; Nirmayanti Syamsuddin; Andi Wilda Resky; Muhammad Resky; Muhammad Fathir Rahmat; Ayu Lestari; Rosdiana Rosdiana; Asriana Asriana; Muhammad Fadryansah; Arman Arifuddin; Muhammad Afdal; Rizal Irfandi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the mother-in-law's tongue (Sansevieria trifasciata) has the potential to remediate Cu contained in the soil. The method used is an experimental method to test the absorption potential of mother-in-law's tongue plant on ground contaminated with Cu metal. The results showed that the samples from days 0, 3, 6, and 9 did not show any changes in the adsorbed metal. The four samples contained the same heavy metal copper (Cu) concentration, which was <0.50 ppm. In conclusion, the mother-in-law's tongue (Sansevieria trifasciata) is not very effective as phytoremediation of soil contaminated with Cu metal but can still be used as phytoremediation. Keywords: Phytoremediation, Sansevieria trifasciata, Copper (Cu)